ANALISIS PEMASARAN KERUPUK KULIT DAN URAT IKAN TUNA DI UD PUTRA SUSILA PASANGGARAN DENPASAR BALI - Ida Ayu Made Dwi Susanti; Ni Putu Anglila Amaral; Dharma Sigith Purnamawan (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
Tuna skin fish crackers are a snack and daily consumption of people in Indonesia. Pasanggaran village is one of the villages in the Denpasar area which is the location for producing tuna skin fish crackers and one of the production centers for tuna skin crackers in Bali because of the condition of the area which is close to the coast of Benoa. The aim of the research entitled ANALYSIS OF MARKETING OF TUNA SKIN AND TIPE CRACKERS AT UD PUTRA SUSILA PASANGGARAN DENPASAR BALI to Increase Income of UD Putra Susila, South Denpasar District, Denpasar City is to find out internal and external factors and alternative marketing strategies for tuna fish skin crackers in increasing income UD Putra Susila. This research was conducted in October-December 2023. The research location was determined using a purposive method while the sample of respondents was determined using a purposive sampling technique with a total of 10 respondents consisting of 1 internal and 9 external. The analysis method in this research uses SWOT analysis. The research results show that, strength factor: Tuna skin fish crackers have good quality and quality, weakness factor: lack of young generation to continue the tuna skin cracker business, opportunity factor: there are many enthusiasts on the island of Bali, threat factor: weather and climate changes